Pengaruh Self Efficacy dan Locus of Control Terhadap Kinerja Guru - Jumiati, Jumiati; Kartiko, Ari (Academicus: Journal of Teaching and Learning, 2022)
The purpose of this study was to determine the effect of self-efficacy and locus of control on teacher performance at SMK Negeri 1 Dlanggu. The method used in this study is a quantitative method. This analysis uses the independent variables self-efficacy and locus of control and the dependent variable is teacher performance. The samples in this study were teachers at SMK Negeri 1 Dlanggu. In this research, the sampling technique that the researcher uses is probability sampling, which uses simple random sampling. The results of this study indicate that self-efficacy and locus of control have a significant effect on teacher performance.